Sexual risk behaviors, mental health outcomes and attitudes supportive of wife-beating associated with childhood transactional sex among adolescent girls and young women: Findings from the Uganda Violence Against Children Survey. - Laura Chiang; Ashleigh Howard; Kirsten Stoebenau; Greta M Massetti; Rose Apondi; Jennifer Hegle; Mondo Kyatekka; Caroline Stamatakis; Lydia Wasula; George Aluzimbi (PLoS ONE)
Compared to young men, Ugandan young women are disproportionately impacted by HIV. Childhood transactional sex may contribute to this disparity. Using data from the 2015 Uganda Violence Against Children Survey, we used logistic regression models to assess the association between childhood transactional sex and negative outcomes. Among 18-24-year-old young women who had sex prior to 18 (n = 982), those who ever engaged in transactional sex had 5.9 times [adjusted odds ratio (AOR); confidence interval (CI): 1.6-22.2] higher odds of having multiple sexual partners in the past year; 5.2 times (AOR; CI: 2.1-12.9) higher odds of infrequent condom use in the past year; 3.0 times (AOR; CI: 1.2-7.9) higher odds of hurting themselves intentionally; and 3.2 times (AOR; CI: 1.3-7.7) higher odds of having attitudes justifying spousal abuse than young women who never engaged in transactional sex. Interventions for transactional sex and HIV in Uganda should consider prioritizing prevention, harm-reduction and continued investment in adolescent girls' and young women's futures.